Assistive Technology: a Health Care Reform for People with Disabilities - Santiago-Pintor, Jorge; Hernández-Maldonado, María; Correa-Colón, Angela; Méndez-Fernández, Héctor L. (Puerto Rico Health Sciences Journal, 2009)
Assistive technology has become one of the most powerful tools in assisting people with disabilities fight for social equality both in Puerto Rico as well as in other cities worldwide. In spite of this, the availability of assistive technology equipment does not constitute reason enough for people with disabilities to have all the technology resources for making them independent and productive in a society as competitive as ours. An assistive technology evaluation process is recommended in order to achieve an optimum level of self-sufficiency in people with disabilities. The evaluation process should take into consideration both the individual’s needs and strength and the advantages and disadvantages of the equipment. The main purpose of this research was to determine the satisfaction level of 69 consumers evaluated at the Assistive Technology Integrated Services Center. These evaluations were conducted during 2001-2005. Statistical tests including distribution of frequencies, chi-square, bivariate and variance analysis were produced in order to determine if a scientific association existed between the consumers’ level of satisfaction with the services and the assisted conditions. The data analysis results showed a significant difference between the satisfaction level with consumer’s age, type of disability, and recommended equipment acquisition. Besides, statistical associations were established between general satisfaction concept dimensions, type of disability, and consumers’ particular characteristics.